PROFIL PENDIDIKAN ANAK USIA DINI - Miftahunnikmah Miftahunnikmah; Ika Ratih Sulistiani; Ika Anggraheni (Jurnal Dewantara, 2020)
Education is the needs and rights of every child. Education is an effort in giving direction in order to change for the better. Early childhood education is a conscious effort to optimize all aspects of development. Sujiono (2013) said early childhood education is an effort to stimulate, guide, nurture, and learning activities that will produce the abilities and skills of children. Parents have an important role in supporting the process of early childhood education. Parents are fully responsible for the education of young children. Parental awareness of the importance of education for early childhood is one of the keys to the successful implementation of early childhood education. Parents are expected to play an active role in preparing early childhood education. This is because early childhood education is the initial foundation to move to the next level of education. As for the busy life of the parents is one of the inhibiting factors in the success of early childhood education.